OVOTESTICULAR DISORDER OF SEXUAL DEVELOPMENT UNMASKED BY ANTIMÜLLERIAN HORMONE: CASE REPORT - A, Saraswathy; Idris , An (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Disorders of sex development (DSDs) including ovotesticular DSD is a group of rare disorders characterized by abnormalities of chromosomal or discordant gonadal phenotype of internal/external genitalia sexes. AntiMüllerian hormone (AMH) which is produced exclusively by the prepubertal immature Sertoli cells can be a useful marker for assessment of testicular function in male sex differentiation. RESULTS We describe a 1 year 7 month child who presented with atypical genitalia noticed since birth and was investigated for adrenal disorders. The child had neither salt losing crisis nor hypoglycaemia symptoms. The term child was the firstborn of non-consanguineous healthy parents. There was no sexual ambiguity, early neonatal deaths or infertility in the extended family. Physical examination revealed healthy and non-dysmorphic child. The child was normotensive with normal growth and neurodevelopment. External genitalia examination revealed a phallus like structure with a single opening at perineum (Prader stage 4). Only the right gonad was descended. The hCG stimulation test showed partial testosterone response. Serum AMH was above the normal age specific female range indicating the existence of testicular tissue. The karyotype cytogenetic analysis showed the genotype of 46 XX with SRY negative. Ultrasound of gonado-pelvis showed presence of uterus and left inguinal hernia containing left ovary and right inguinal gonad resembling testis. The child was provisionally diagnosed as 46XX ovotesticular DSD. CONCLUSION This case revealed the importance of serum AMH as a marker in the evaluation of ovotesticular DSD. The utilization of basal testosterone and gonadotropin stimulation have limited use in the assessment of prepubertal DSD. Serum AMH may provide earlier information in the differential diagnosis of DSDs. Continuous high secretion of AMH by Sertoli cells in a sexually dimorphic pattern during infancy and childhood with high levels in boys and low levels in girls makes AMH such an appealing biomarker of testicular function, henceforth a prior gonadotropin stimulation may not be required in the assessment of DSD cases.